Regulation of Isoflavone Biosynthesis by miRNAs in Two Contrasting Soybean Genotypes at Different Seed Developmental Stages - Gupta, Om P.; Nigam, Deepti; Dahuja, Anil; Kumar, Sanjeev; Vinutha, T.; Sachdev, Archana; Praveen, Shelly (Frontiers in Plant Science, 2017)
Owing to the presence of nutritionally important, health-promoting bioactive compounds, especially isoflavones, soybean has acquired the status of a functional food. miRNAs are tiny riboregulator of gene expression by either decreasing and/or increasing the expression of their corresponding target genes. Despite several works on identiﬁcation and functional characterization of plant miRNAs, the role of miRNAs in the regulation of isoflavones metabolism is still a virgin field. In the present study, we identified a total of 31 new miRNAs along with their 245 putative target genes from soybean seed-specific ESTs using computational approach. The Kyoto Encyclopedia of Genes and Genomes pathway analyses indicated that miRNA putatively regulates metabolism and genetic information processing. Out of that, a total of 5 miRNAs (Gma-miRNA12, Gma-miRNA24, Gma-miRNA26, Gma-miRNA28 and Gma-miRNA29) were predicted and validated for their probable role during isoflavone biosynthesis. We also validated their five target genes using RA-PCR, which is as good as 5’RLM-RACE. Temporal regulation (35DAF, 45DAF, 55DAF and 65DAF) of miRNAs and their targets showed differential expression schema. Differential expression of Gma-miR26 and Gma-miRNA28 along with their corresponding target genes (Glyma.10G197900 and Glyma.09G127200) showed a direct relationship with the total isoflavone content. Therefore, understanding the miRNA-based genetic regulation of isoflavone pathway would assist in selection and manipulation to get high-performing soybean genotypes with better isoflavone yield.